Indian accents : brown voice and racial performance in American television and film - Davé, Shilpa (Urbana : University of Illinois Press, 2013)
"The representation of Indian Americans as foreign terrorists and as citizens who speak with an American accent comprise a major plot point in Harold and Kumar Escape From Guantanamo Bay. In American media, South Asians vacillate between being cast as racially foreign while simultaneously being praised as a model minority because they are highly educated, speak English, and can economically succeed in America. In American cinema and television, Shilpa Davé serves how contemporary images of South Asians build upon, modify, and at times diverge from previous stereotypes of Asian Americans as immigrants and model minorities"--
""5. The (Asian) American Dream: Harold and Kumar Go to White Castle and the Pan-Ethnic Buddy Film""""6. ""Running from the Joint"": Harold and Kumar Escape from Guantanamo Bay and Comic Narrative after 9""; ""Epilogue""; ""Notes""; ""Index""
Includes bibliographical references and index.
Description based on print version record.
English.
JSTOR
Keywords: Accents and accentuation in motion pictures; Accents and accentuation in television programs; East Indians in motion pictures; Motion pictures -- United States; Television programs -- United States; English language -- United States -- Pronunciation by foreign speakers; Cinéma -- États-Unis.; Émissions télévisées -- États-Unis.; Anglais (Langue) -- États-Unis -- Prononciation par des allophones; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; SOCIAL SCIENCE -- Ethnic Studies -- Asian American Studies; Accents and accentuation in motion pictures; Accents and accentuation in television programs; East Indians in motion pictures; English language -- Accents and accentuation; English language -- Pronunciation by foreign speakers; Motion pictures; Television programs; United States; Electronic book